Synthesis, Characterization, and Biological Activities of Rare Earth Metal Complexes with Gallic Acid - Nguyen Thi Hien Lan; Hoang Phu Hiep; Dinh Cong Trinh; Pham Van Khang (Inorganics)
This study reports the synthesis and characterization of four novel rare earth-gallic acid complexes, Sm(Gal)3·4H2O, Eu(Gal)3·4H2O, Tb(Gal)3·4H2O, and Dy(Gal)3·4H2O. These complexes were synthesized under optimized conditions (60 °C, pH 4–5) and characterized using the Ln3+ elemental content method, infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), mass spectrometry (MS), and fluorescence spectroscopy. IR spectra confirmed the coordination of rare earth ions (Ln3+) with gallic acid through carboxylate oxygen atoms. TGA revealed the thermal decomposition pathways, while MS identified the molecular ion peaks and fragmentation patterns. All complexes exhibited strong luminescence under UV excitation, with emission peaks corresponding to characteristic transitions of Sm3+, Eu3+, Tb3+, and Dy3+. Biological assays demonstrated significant antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa, with Dy(Gal)3·4H2O showing the highest efficacy. Additionally, the complexes displayed inhibitory effects on MCF7 breast cancer cells, with Tb(Gal)3·4H2O exhibiting the lowest IC50 value (11.3 µM). These findings suggest that rare earth metal complexes with gallic acid have potential applications in biomedical fields, particularly as antimicrobial and anticancer agents.